Modelling and Simulation of Chemical Adsorption Heat Pump for Drying and Heating Applications - ISOLA, Abimbola Emmanuel; OLAKUNLE, Michael Sunday; OLAWALE, Adegboyega Surajudeen (ABUAD Journal of Engineering and Applied Sciences, 2024)
The performance of a chemical adsorption heat pump drying system is largely influenced by the selection of working fluid, operating conditions, and system configuration and design. In this study, tomato slices were dried at five different air temperatures (35 °C, 40 °C, 45 °C, 50 °C, and 55 °C) with a tomato slice flow rate of 400 kg/hr and an air flow rate of 200 kg/hr using a modelled and simulated chemical adsorption heat pump drying system. Four adsorbent-adsorbate pairs were used: magnesium chloride-methanol, calcium chloride-ethanol, calcium chloride-water, and aluminium trifluoride-dimethyl ether, at evaporating and condensing temperatures of 10 °C and 15 °C, respectively. The specific moisture extraction rate ranged from 0.116 kg/kWh to 0.149 kg/kWh. The coefficient of performance (COP) of the heat pump drying (HPD) system ranged from 0.960 to 0.987, and the overall exergy efficiency at the highest ambient air temperature (30 °C) ranged from 3.84% to 20.29%. Exergy analysis of the system's components revealed that the condenser and evaporator contributed significantly to exergy destruction, exhibiting low exergy efficiency.